Common Fixed Point Results for Four Mappings on Partial Metric Spaces. (4th October 2012) - Turkoglu, A. Duran; Ozturk, Vildan
Abstract : We give fixed point results for four mappings which satisfy almost generalized contractive condition on partial metric space and we support the results with an example.